(untitled) (INTEK : Jurnal Informatika dan Teknologi Informasi, 2026)
This study explored the adoption of Artificial Intelligence (AI) in Indonesian workplaces and productivity-related environments by examining user experience, trust, and ethical governance across enterprise-integrated systems and general AI tools. The study used a quantitative survey involving 74 respondents consisting of students, workers, freelancers, and other productive-age groups. The results showed that 56.8% of respondents experienced lag at least “Sometimes” when using AI-based features. In terms of trust, 81.1% of respondents prioritized accuracy and 74.3% prioritized transparency in AI systems. Additionally, 91.9% stated that explainability features could improve trust toward AI systems. The findings also revealed the emergence of a mixed AI ecosystem, where 43.2% of respondents used a combination of AI and productivity tools in daily activities. Based on these findings, this study proposed a human-centered AI governance approach supported by the NIST AI Risk Management Framework and ISO/IEC 42001 to encourage more responsible and trustworthy AI adoption in Indonesian organizations.